Bangali Handwritten characters classification using Deep Convolutional Neural Network - Sikder, Shihab Uddin; Muslebeen, Md. Shafiul (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.